Positive Reinforcement-Based Training for Self-Loading of Meat Horses Reduces Loading Time and Stress-Related Behavior - Dai, Francesca; Dalla Costa, Alessandro; Bonfanti, Lebana; Caucci, Claudia; Di Martino, Guido; Lucarelli, Roberta; Padalino, Barbara; Minero, Michela (Frontiers in Veterinary Science, 2019)
The present work aimed to evaluate the efficacy of a self-loading training using positive reinforcement on stress-related behaviors shown by meat horses during loading procedures into a truck. Thirty-two meat horses (M=18; F=14; 6 month-old) were included in the study. All horses had limited interactions with the farmer and were not used to be restrained nor lead by halter. Horses were divided in two groups: Control Group (C; N=14) and Training Group (T; N=18). T horses were trained to self-load: in order to teach the horses to enter into the truck, a targeting training technique throughout a shaping process was applied. Training sessions were performed three times a week, from 9:30 am to 1:30 pm and from 2:30 pm to 4:30 pm, for six weeks; training was then repeated once a week to maintain the memory until the transport toward a slaughterhouse. The loading phase was video-recorded and loading time was directly recorded using a stopwatch. All horses were transported to the same slaughterhouse in fourteen different days using the same truck. Behavior was subsequently analyzed with a focal animal continuous recording method. Loading time was shorter in T horses (mean±SD = 44.44±47.58 seconds) than in C horses (mean±SD = 463.09±918.19 seconds) (T test; p=0.019). T horses showed more forward locomotion towards the truck than C horses (T test; p=0.029). Our preliminary findings suggest that self-loading training may be useful to mitigate loading-related stress in meat horses, minimally socialized with humans.